PPUPIK PRODUKSI BENIH KEDELAI BERSERTIFIKAT DI POLITEKNIK PERTANIAN NEGERI KUPANG - Lewar, Yosefina; Hasan, Ali; Salli, Maria Klara; Sengaji, Haryati (Universitas Tanjungpura, 2019)
Soybean is an important commodity as a source of protein, raw material for various food industries and animal feed ingredients. Some of the factors that have led to an increase in domestic soybean demand are increased public awareness of nutrition and protein, increasingly high prices for animal-based side dishes, widespread use and export of soy sauce, and the shifting of the soybean processing industry from home industries to medium to large industries. This is also supported by one of the government programs since 2017-2021, namely the development of soybean plants nationally. The development of these commodities certainly requires the right quality seed, quantity, place, time, and price. With the rolling of the business program to increase production of each commodity, the potential need for quality seeds is quite large. The need for developing soybean seeds in ENT is quite high. Kupang State Politics as a vocational education institution in agriculture needs to develop a business unit for raising soybean seeds. This PPUPIK activity was carried out in 2018-2020 and after PPUPIK in 2021 it has the aim of making theÂ State Agricultural Polytechnic of Kupang a center for certified soybean seed production that is commercial and available continuously.Â Keywords: seeds, soybean, certified, PPUPIK, ENT